Upaya Pemerintah Indonesia Dalam Menangani Kasus Perdagangan Orang: Studi Kasus Pengantin Pesanan (Mail-Order Brides) Indonesia–China - Ariella A. Yoteni (Papua Journal of Diplomacy and International Relations, 2021)
This article examines the extent to which the Indonesian government has made efforts in handling the Mail-Order Brides (MOB) Indonesia–China as part of trafficking in persons. Indonesia has been a country of origin, transit, and destination for victims over the years, thereby making this topic crucial. This study adopted a qualitative descriptive analysis, whilst data collection techniques were library research and online research. This article found that the Indonesian government had been effective in solving the MOB cases. The efforts, undertaken by the Ministry of Foreign Affairs, the Directorate General of Immigration, and the Chinese Embassy in Jakarta, had contributed significantly to the case study–where nearly 80% of the total cases reported between 2015 and 2019 were successfully resolved. In so doing, the Indonesian government also faced challenges; one of which was the lack of cooperation from the Chinese government– differences in views in the MOB cases. The results of this study include recommendations for public awareness campaigns for MOB, integration of transnational crime subjects in the education curriculum, and so forth.                                            KEYWORDSChina; Indonesia; Mail-Order Brides; Trafficking